Antimicrobial enhancement via Cerium (II)/Lanthanum (III)‐doped TiO₂ for emergency leak sealing polyurea coating system - Li, Yuanzhe (2023)
Industrial piping structures often suffer from corrosion caused by biofouling or chemical etching, which can cause immediate structural failure. Polyurea coatings, which are fabricated for emergency leak sealing, are able to form high mechanical strength coating surfaces within seconds. After its further modification via Ce/La-doped TiO2, the polyurea coating will indicate an increment in mechanical strength, chemical durability, and reduction of microbial attachment. Due to the adsorption by the Ce/La-doped TiO2 and generation of reactive oxygen species (ROS), E. coli and Pseudomonas may lose their living conditions during the progress, and planktonic bacteria cells are prevented from enriching on the surface. The Ce/La‐dopants can also improve the original photocatalytic response of nano-TiO2 to UV light and environmental temperature. These Ce/La-doped TiO2 polyurea coatings illustrate an immediate application for emergency leak sealing purposes without any production interruption and it may prolong the time intervals for the maintenance service as well.